Rethinking Learning Design in IT Education During a Pandemic - Pappas, Ilias O.; Giannakos, Michail N. (Frontiers in Education, 2021)
Maintaining high-quality teaching and learning in the times of a pandemic poses a huge challenge to education systems. To scaffold adequate practices in our courses during the pandemic, more advanced and fine-grained ‘learning design’ is needed than providing the learning objectives and learning materials of the course and defining the deliverables and assignments. In this paper, we leverage on our experience with putting into practice different learning designs and technologies, in various IT contexts and discuss how IT educators can further reflect on the learning design of their courses and scaffold fully remote or blended learning approaches to accommodate their courses' needs during the pandemic. We provide three important objectives and indicative technological solution that can support those objectives, and discuss some lessons learned from our experience.